Comparative Study of Sugars, Organic Acids and trans-Resveratrol in Red and White Grapes Grown in Denizli Region, Turkey - Otag, M.; Kadakal, C. (Asian Journal of Chemistry, 2015)
Grape berry ripening includes a broad range of physical and biochemical processes. In this study, compare the changes in organic acid, sugar and trans-resveratrol content during at four different ripening stages (lag phase, veraison, maturity and late harvest) between red (Çalkarasi and Shiraz) and white (Sultana and Round Seedless) grapes grown in Denizli region were investigated. Analysis was carried out using the high performance liquid chromatography-diode array detector (HPLC-DAD). Glucose and fructose content was increased between lag phase stages and late harvest stages. Tartaric and malic acid content of all cultivars decreased throughout the maturation period. A continuous decrease in trans-resveratrol content in all varieties was observed during ripening.